Design of a wing for an unmanned aircraft using non-linear lifting-line numerical method - 303014 Tan, Kae Yuan (Sekudai : UTM, 1997)
Project Paper (Bachelor of Mechanical Engineering) - Universiti Teknologi Malaysia, 1997